A cooperative uplink power control scheme for elastic data services in wireless CDMA systems. - Alyfantis, George (Computer communication review.)
We consider the uplink power control problem in a single cell CDMA wireless data system. Each user specifies upper and lower QoS bounds. We formulate the considered problem as a game, and first examine the non-cooperative case. We then compare it to its cooperative counterpart (through the Nash bargaining solution). The use of the cooperative scheme shows significant reduction in the transmission power of the mobile terminals, while the achieved QoS is slightly compromised, compared to the non-cooperative scheme.